2015
DOI: 10.13075/ijomeh.1896.00398
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral hypermobility of ulnar nerves at the elbow joint with unilateral left ulnar neuropathy in a computer user: A case study

Abstract: Occupational ulnar neuropathy at the elbow joint develops in the course of long term direct pressure on the nerve and a persistently flexed elbow posture, but first of all, it is strongly associated with "holding a tool in a certain position" repetitively. Therefore, computer work only in exceptional cases can be considered as a risk factor for the neuropathy. Ulnar hypermobility at the elbow might be one of the risk factors in the development of occupational ulnar neuropathy; however, this issue still remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The difference in the incidence rates of ulnar nerve dislocation between the healthy subjects and patients with UNE has not been established yet (Lewanska, Grzegorzewski & Walusiak-Skorupa, 2016). Previous studies of investigating the ulnar nerve dislocation in patients with UNE reported that the ulnar nerve partial and complete dislocation were occurred in 14–18.7% and the 6.7–9.9%, respectively (Filippou et al, 2010; Van Den Berg et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in the incidence rates of ulnar nerve dislocation between the healthy subjects and patients with UNE has not been established yet (Lewanska, Grzegorzewski & Walusiak-Skorupa, 2016). Previous studies of investigating the ulnar nerve dislocation in patients with UNE reported that the ulnar nerve partial and complete dislocation were occurred in 14–18.7% and the 6.7–9.9%, respectively (Filippou et al, 2010; Van Den Berg et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the ulnar nerve dislocation was associated with tardy ulnar palsy in cubitus varus deformity (Jeon et al, 2006). A previous case study had suggested that the abnormal dislocation of the ulnar nerve during elbow flexion increased the possibility of its mechanical injury (Lewanska, Grzegorzewski & Walusiak-Skorupa, 2016). The dynamic US scan is an optimal tool for the assessment of ulnar nerve dislocation (Chuang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to several studies, UNI is a risk factor for ulnar neuropathy. 23,24 Schertz et al 23 evaluated the morphological and dynamic differences in the nerves in patients with and without ulnar neuropathy and found that the frequency of ulnar neuropathy was significantly higher in the dislocated than the control group. Kang et al 7 25 the CSA values were significantly higher in the unstable group; Ozturk et al 18 reported similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Among users of hanging cabinets, older adults face more serious physical problems ( Lewanska et al, 2016 ). Tasks such as opening and closing doors and pulling out drawers in hanging cabinets, bookcases, and other furniture cause significant changes in body parts, such as bending, stretching, and lifting ( Richter-Kluge et al, 2019 ; Norin et al, 2021 ; Simundic et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%